Examining Health Disparities in Orthopedic Care During COVID-19. Issue 4 (April 2023) - Pond, Kristina; Samuels, Kaitlyn; Meinhardt, Gerek; Jacobs, Cale
Background: Demographics and socioeconomic status affect the delivery of medical care resulting in healthcare disparities. The purpose of this study was to investigate the impact of COVID-19 on existing healthcare disparities, including access to healthcare in the outpatient orthopedic surgery clinic. Methods: The medical records of 3006 patients treated at the University of Kentucky Orthopedic Surgery Department prior to COVID-19 (April 2018, 2019), and during the COVID-19 pandemic (2020) were retrospectively reviewed for demographic data, distance to clinic, and type of visit. We then compared the total number of patient visits, new patient visits, telehealth visits, and the patient's insurance provider (public or private) between the time period prior to and during the pandemic. Results: During the COVID-19 pandemic, there were significant declines in the number of patients seen, new patient presentations, and publicly insured patients. Thirty-three percent of visits were telemedicine visits in 2020 compared to 0% pre-COVID ( P < .0001). There was a lower proportion of initial visits in 2020 ( P < .0001). The majority of patients paid via private/commercial insurance (1798, 59.8%), with a greater proportion paying via private/commercial insurance in 2020 ( P < .001). The median average household income was increased in 2020 ( P < .001). Discussion: While COVID-19 resulted in a significant decline in overall access to care, there were negative ramifications particularly on patients with new complaints and those of lower socioeconomic status. Future endeavors should be focused on correcting the obstacles to accessing care, exacerbated by the pandemic, that these vulnerable populations face.